2003
DOI: 10.1046/j.1525-1594.2003.07106.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of S‐Nitroso‐Glutathione on Platelet and Leukocyte Function During Experimental Extracorporeal Circulation

Abstract: Treatment with extracorporeal membrane oxygenation ECMO) is associated with side effects, e.g., blood cell consumption and activation. Our group has earlier shown that nitric oxide administered as a gas reduces platelet consumption and activation. In the present work we have studied the effect of the NO-donor S-nitroso-glutathione GSNO) on platelets and leukocytes in an in vitro extracorporeal circuit. Two complete ECMO circuits were perfused with fresh heparinized human blood for 24 hours. GSNO was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Previous work, including ours, has established that NO releasing polymers (NORel) can prevent loss of circulating platelets and monocytes in the RT model and limited clinical ECLS [6, 27, 28]. These experiments demonstrate significant evidence for the importance of NO in defining, in part, the hemocompatibility of biomaterials used in ECLS and mimicking NO released from normal functioning vascular endothelium.…”
Section: Discussionsupporting
confidence: 53%
“…Previous work, including ours, has established that NO releasing polymers (NORel) can prevent loss of circulating platelets and monocytes in the RT model and limited clinical ECLS [6, 27, 28]. These experiments demonstrate significant evidence for the importance of NO in defining, in part, the hemocompatibility of biomaterials used in ECLS and mimicking NO released from normal functioning vascular endothelium.…”
Section: Discussionsupporting
confidence: 53%
“…and partially observed by Ki et al. ( 32 , 33 , 37 ). The discrepancies between the outcomes could be rationalized by the utilization of different ECMO technology, model setup, and blood flow rates.…”
Section: Ecmo As a Second “Hit” To Leukocyte Pathophysiology In Critimentioning
confidence: 61%
“…However, the effect of ECMO on L-selectin (CD62L), another key adhesion molecule, remains debatable. Three studies independently reported either a reduced, augmented, or no change in expression of L-selectin at the initial hours of ECMO ( 18 , 32 , 33 ). Observed discrepancies may be associated with the differences between human, porcine and ex vivo ECMO.…”
Section: Ecmo As a Second “Hit” To Leukocyte Pathophysiology In Critimentioning
confidence: 99%
See 1 more Smart Citation
“…Katrin Adrian et al of The Queen Silvia Children's Hospital (Göteborg, Sweden) studied the effect of nitric oxide‐donor S‐nitroso‐glutathione (GSNO) on platelets and leukocytes in an in vitro extracorporeal circuit (138). No significant effect of GSNO on circulating platelets or leukocytes during experimental extracorporeal circulation was shown indicating that a continuous infusion of GSNO would probably not be helpful during clinical cardiopulmonary bypass on ECMO.…”
Section: Extracorporeal Circulation and Membrane Oxygenationmentioning
confidence: 99%